Comparative Analysis of Behavioral Theories in Promoting CPR: A Theory-Based Approach to Cardiopulmonary Resuscitation Training in Community - Abdurahman Wahid; Dina Septiany; Sri Widati; Sri Haryuni; Nurma Afiani; Novita Ana Anggraini (Postgraduate, University of Mataram, 2025)
Sudden cardiac arrest (SCA) is a critical emergency that need immediate intervention to prevent death. This review will discuss behavioral theories relevant to the promotion of Cardiopulmonary Resuscitation in the community. Findings from previous studies were analyzed using approaches from three theories, namely the Integrated Behavior Model (IBM), Health Belief Model (HBM), and Social Cognitive Theory (SCT). This narrative review examines three behaviour theories applicability as a conceptual model for CPR promotion, focusing on enhancing community engagement and response rates to out-of-hospital cardiac arrests (OHCA). Articles search keywords used for review including